Effect of Low Intensity Transcranial Ultrasound (LITUS) on Post-traumatic Brain Edema in Rats: Evaluation by Isotropic 3-Dimensional T2 and Multi-TE T2 Weighted MRI - Zheng, Tao; Du, Juan; Yuan, Yi; Wu, Shuo; Jin, Yinglan; Shi, Qinglei; Wang, Xiaohan; Liu, Lanxiang (Frontiers in Neurology, 2020)
Background: Brain edema is one of the important factors affecting the prognosis of traumatic brain injury (TBI). Low-intensity transcranial ultrasound (LITUS) has significant anti-cerebral edema effect. T2-weighted image-based volume and T2 value measurements can sensitively reflect tissue edema. Purpose: To evaluate the effect and possible mechanisms of LITUS on brain edema by iso-voxel 3-dimensional T2WI (iso-3D T2WI) and multi-TE T2WI. Methods: Forty-five rats were randomly divided into sham control, TBI and TBI＋LITUS groups (n=15, respectively). Iso-voxel 3-dimensional T2WI and multi-TE T2WI sequences at 3.0T to obtain T2 value and edema volume of the injury cortex. T2 values were obtained on days 1, 7, 14, 21, 28, 35 and 42 after TBI and brain edema volume were obtained on days 7 and 14. Results: The T2 values of the damaged cortex in the TBI group showed a slow decreasing trend after a significant increase. For TBI+LITUS group, T2 values decreased with continuous LITUS treatment. At day 28, the T2 values were not significantly longer than the control group (adjusted P=0.0535), but were significantly shorter than the TBI group at day 42 (adjusted P=0.0003). The edema volume at day 7 and 14 in the LITUS group was significantly lower than the TBI group (P=0.0004 and P<0.0001, respectively). AQP-4 and β-APP protein staining showed a strong positive reaction near the CCI point, TBI+LITUS group showed a medium positive reaction, and the sham control group showed a weak positive reaction. Conclusion: The therapeutic effect of LITUS on post-traumatic brain edema was confirmed through T2 value and edema volume, and the mechanism may be related to inhibiting the expression of AQP-4 and promoting the removal of β-APP.